Asymmetric effects of inflation on economic growth in the Sultanate of Oman - Shehab, Ayman Al; Farsi, Maryam Al (Asian Journal of Economic Modelling, 2024)
This study examines whether the effects of inflation on Oman's economic growth are symmetric or asymmetric, aligning with Oman Vision 2040's goal of sustained economic growth and controlled inflation. The literature has shown significant variations in assessing the impact of inflation on economic growth. Quarterly data from Q1 2010 to Q4 2022 were analyzed using the linear autoregressive distributed lag (ARDL) and the nonlinear autoregressive distributed lag (NARDL) models to explore whether the relationship between inflation and economic growth in Oman is symmetric or asymmetric. The results reveal that inflation and economic growth in Oman are nonlinearly cointegrated. Inflation has asymmetric effects: rising inflation positively impacts economic growth while decreasing inflation negatively affects it. This asymmetry holds in both the short- and long-run. The study concludes that inflation’s impact on Omani economic growth is asymmetric, with increases in it having a stronger positive effect than decreases. These findings enhance our understanding of the dynamics between inflation and growth in Oman, an area where nonlinear studies have been underrepresented. The insights from this study can guide policymakers in shaping inflation control strategies that support economic growth, aligning with Oman Vision 2040's objectives for sustainable development.